2018
DOI: 10.1073/pnas.1719354115
|View full text |Cite
|
Sign up to set email alerts
|

Extrachromosomal circular DNA-based amplification and transmission of herbicide resistance in crop weed Amaranthus palmeri

Abstract: SignificanceGlyphosate is a nonselective herbicide used around the globe for weed control in glyphosate-resistant (GR) and noncrop situations. The extensive and exclusive use of glyphosate has led to the evolution of herbicide resistance in many crop weeds. The molecular target of glyphosate, the 5-enolpyruvlyshikimate-3-phosphate synthase (EPSPS) gene, confers resistance upon amplification and was first documented in GR Amaranthus palmeri. We now report that amplified EPSPS copies in GR A. palmeri are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
241
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(254 citation statements)
references
References 56 publications
10
241
0
3
Order By: Relevance
“…Studies on the molecular biology and physiology of glyphosate resistance in several weed species have contributed to a broader and deeper understanding of herbicide resistance evolution. For evolved glyphosate‐resistant weeds, resistance mechanism studies reveal EPSPS gene amplification (Gaines et al ., a; Jugulam et al ., ; Patterson et al ., ) through the inheritance of replicating extrachromosomal circular DNA molecules (Koo et al ., ,b), EPSPS transcriptional regulation (Zhang et al ., ), EPSPS double mutants (Funke et al ., ; Sammons & Gaines, ; Chen et al ., , ; Yu et al ., ; Sauer et al ., ; Hummel et al ., ; Sammons et al ., ) and vacuolar sequestration of glyphosate via ABC transporters, with the dependence of this process on light (Sharkhuu et al ., ) and temperature (Ge et al ., ). The substantial research effort that continues to reveal glyphosate resistance mechanisms/mutations reflects that glyphosate is the most globally used herbicide and highlights the intriguing evolutionary pathways used by weed species to resist glyphosate.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…Studies on the molecular biology and physiology of glyphosate resistance in several weed species have contributed to a broader and deeper understanding of herbicide resistance evolution. For evolved glyphosate‐resistant weeds, resistance mechanism studies reveal EPSPS gene amplification (Gaines et al ., a; Jugulam et al ., ; Patterson et al ., ) through the inheritance of replicating extrachromosomal circular DNA molecules (Koo et al ., ,b), EPSPS transcriptional regulation (Zhang et al ., ), EPSPS double mutants (Funke et al ., ; Sammons & Gaines, ; Chen et al ., , ; Yu et al ., ; Sauer et al ., ; Hummel et al ., ; Sammons et al ., ) and vacuolar sequestration of glyphosate via ABC transporters, with the dependence of this process on light (Sharkhuu et al ., ) and temperature (Ge et al ., ). The substantial research effort that continues to reveal glyphosate resistance mechanisms/mutations reflects that glyphosate is the most globally used herbicide and highlights the intriguing evolutionary pathways used by weed species to resist glyphosate.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…Our results are consistent with those of recent research which showed that EPSPS protein levels did not differ between RR glyphosate‐resistant and ‐susceptible A. trifida accessions from Indiana . Increased EPSPS copy number has been reported in many other glyphosate‐resistant species including Palmer amaranth ( Amaranthus palmeri S. Watson ), waterhemp [ A. tuberculatus (Moq.) J. D. Sauer], spiny amaranth ( A. spinosus L.), ripgut brome ( Bromus diandrus Roth), windmillgrass ( Chloris truncata R.…”
Section: Resultsmentioning
confidence: 99%
“…The eccDNAs are universally spread in eukaryotes, including plants (1, 2), yeasts (3, 4) and mammalians (57). Contrast to the more stable linear DNA on the chromosomes, the eccDNAs are extrachromosomally located, unstable, dynamic, and heterogeneously originated.…”
Section: Overview Of Eccdnasmentioning
confidence: 99%